Numerical and Experimental Study on Combustion Characteristics of Micro-Gas Turbine Biogas Combustor - Aiguo Liu; Ruiyang Fan; Qiaochu Liu; Lei Xi; Wen Zeng (Energies, 2022)
The use of biogas in land-based gas turbines for power generation is a promising approach to reducing greenhouse gases and our dependence on fossil fuels. The focus of this research was to investigate the fuel/air mixing and combustion performance in an DLE (dry low emission) type can combustor designed for a micro-gas turbine. The fuel and air mixing uniformity was studied considering the air flow characteristic and fuel injection performance through the numerical simulation. The influence of the fuel/air mixing characteristics on the combustion characteristics was studied by numerical simulation and experimental tests. The combustion characteristics studied included the temperature field in the combustor, the pattern factor at the combustor outlet, combustion efficiency, and pollutant emission characteristics. The results show the position of the fuel nozzle has little effect on the mixing uniformity due to the limited mixing space for the micro-gas turbine combustor, while there are optimal fuel nozzle diameters to generate the suitable fuel jet momentum for the mixing process. The fuel/air mixing characteristics had an obvious influence on the combustion performance for the studied DLE combustor. The increase in the fuel air mixing uniformity can decrease the NOx emissions and generate a better temperature distribution at the combustor outlet. The increased mixing uniformity may decrease the combustion efficiency and increase the CO emissions of the micro-gas turbine combustor.